Carotid atherosclerosis, dilation, and stiffness relate to cerebral small vessel disease. (28th April 2020) - Zhai, Fei-Fei; Yang, Meng; Wei, Yao; Wang, Ming; Gui, Yang; Han, Fei; Zhou, Li-Xin; Ni, Jun; Yao, Ming; Zhang, Shu-Yang; Jin, Zheng-Yu; Cui, Li-Ying; et al.
Abstract : Objective: To investigate the association of carotid atherosclerosis, dilation, and stiffness with imaging markers of cerebral small vessel disease (CSVD) in a community-based sample. Methods: The study comprised 1, 051 participants (age 57.5 ± 9.2 years). Carotid plaques, intima-media thickness (IMT), diastolic diameter, pulse wave velocity, and stiffness index (β) were measured by ultrasound. Imaging markers of CSVD, including lacunes, cerebral microbleeds, dilated PVS, and white matter hyperintensities (WMH) volume, were assessed. Results: Carotid plaque was associated with the presence of lacunes (odds ratio [OR] 2.78, 95% confidence interval [CI] 1.78–4.33; p < 0.001) and larger WMH volume (natural log transformed, β ± SE, 0.32 ± 0.10; p = 0.002). The increased carotid diameter was associated with the presence of lacunes (OR 1.82, 95% CI 1.22–2.72; p = 0.003), larger WMH volume (β ± SE, 0.37 ± 0.10; p < 0.001), and PVS in the basal ganglia (OR 1.59, 95% CI 1.20–2.11; p = 0.001). Associations of carotid dilation and CSVD were independent of carotid IMT and plaque. Most parenchymal lesions were located in the basal ganglia and deep white matter. Carotid IMT and stiffness were not associated with CSVD. Conclusions: Carotid atherosclerosis and dilation are associated with imaging markers of CSVD. The noninvasive carotid assessment would seem to be a rational approach to risk stratification of CSVD.